Principles of geochemical prospecting : techniques of prospecting for non-ferrous ores and rare metals - Ginzburg, I. I. (Ilia Isaakovich), 1882-1965 (International series of monographs on earth sciences, 1960)
International Series of Monographs on Earth Sciences, Volume 3: Principles of Geochemical Prospecting: Techniques of Prospecting for Non-Ferrous Ores and Rare Metals covers the developments of theoretical premises of geochemical prospecting based on existing theories of endogenic and exogenic ore-formation. This volume is divided into 13 chapters, and begins with a presentation of the problems originating in geochemical prospecting. The next chapters evaluate the relative importance of different prospecting methods. Considerable chapters are devoted to a generalized view of prospecting work in.